IMPLEMENTASI PENGAWASAN UJI KOMPETENSI AKUNTANSI DI SMK SATU NUSA LAMPUNG : TANTANGAN, PROSFEK MASA DEPAN - Muhammad Junaidi; Marlia Sari; Ketut Partayasa; Muhammad Rasid (MUHKAL, 2024)
Supervision of competency exams in vocational high schools (SMK) has a crucial role in maintaining the integrity of education and ensuring that the student evaluation process takes place fairly and accurately. This study aims to explore the practice of supervising competency exams at SMK Satu Nusa Lampung, as well as to understand the perceptions and challenges faced by relevant stakeholders. The research method used is a qualitative study with data collection through in-depth interviews with teachers, students and school administration staff, as well as direct observation of the exam supervision process. The results show that exam proctoring practices involve a variety of methods, including supervision by supervising teachers, the use of surveillance cameras, and anti-plagiarism software. The main challenges in exam supervision include limited resources and students' lack of compliance with supervision rules. Based on these findings, it is recommended to increase training for supervisory teachers, allocate greater funds for supervision technology, and integrate character and ethics education into the school curriculum to increase students' awareness of academic integrity.